The mechanisms of activation of the single chain cytokine receptors: preformed and ligand-induced dimerization - Gryshkova, V.S.; Albu, R.I.; Constatinescu, S.N. (Вiopolymers and Cell, 2014)
Despite intensive studies, the mechanisms of cytokine receptor activation are still not completely understood. Historically two models have been proposed: early studies suggested a mechanism involving ligand-induced di- merization of the receptors which results in the activation of downstream signaling pathways, whereas, in the absence of ligands, the receptors are thought to be in a monomeric inactive state; later studies uncovered evidence for the existence of many receptors as inactive preformed dimers, which upon ligand binding undergo conformational changes and/or relative rotation of the receptor molecules. Here we focus on the dimerization status of the single chain cytokine receptors, which are involved in the regulation of hematopoiesis.